Exploring Regional Disparities and Stakeholder Engagement in Slovenian EIP-AGRI Projects - Mikolič, Sara; Potočnik Slavič, Irma (Journal for Geography, 2025)
The European Innovation Partnership for Agricultural Productivity and Sustainability (EIP-AGRI) was introduced to enhance EU’s capacity for agricultural innovation by bridging the gap between research and practise. This paper explores the implementation of EIP-AGRI Operational Groups (OGs) in Slovenia, focusing on their spatial distribution, stakeholder networks and thematic priorities. Findings indicate multi-actor participation. However, farmers often take on a passive role in innovation processes and a linear knowledge transfer model persists. Strengthening their position as co-creators of innovations could improve its applicability and long-term impact. Environmental sustainability and climate adaptation are a key thematic priority, but project selection remains administratively driven rather than reflecting bottom-up stakeholder needs. A higher concentration is found in the Eastern Cohesion Region and Central Slovenia, likely due to agriculture’s role, farm density, as well as support networks, including agricultural educational and research institutions and advisory services.
Keywords: EIP-AGRI Operational Groups; agricultural innovation; multi-actor projects; stakeholder networks; Slovenia; innovation policies; agricultural policies